A Digital Platform on Climate-Resilient Crops and Varieties Available in CGIAR Centers: Survey questionnaire - International Potato Center (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Background: The International Potato Center (CIP) under the project “Policy Imperatives for Southeast Asia’s Regional Food Systems Under Climate Change” with funding from CCAFS is working on developing a digital platform on climate-resilient crops and varieties released by and available in CGIAR center. Objective: To develop a digital platform for exchange of information and data on the need and availability of climate-resilient crops and varieties from the CGIAR centers.